1985
DOI: 10.1113/jphysiol.1985.sp015844
|View full text |Cite
|
Sign up to set email alerts
|

The effects of pregnancy and parturition on phosphorus metabolites in rat uterus studied by 31P nuclear magnetic resonance.

Abstract: SUMMARY1. Concentrations of phosphorus metabolites and intracellular pH have been measured in non-pregnant, late-pregnant and post-partum rat uterus using 31P nuclear magnetic resonance (31P n.m.r.). Intact uterine tissue was superfused with oxygenated de-Jalon solution at 4, 20 or 37 TC while inside the n.m.r. spectrometer.2. The phosphocreatine concentration [PCr], was higher and the inorganic phosphate concentration [Pi], lower than values determined by chemical analysis of extracts from both pregnant and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
38
2

Year Published

1990
1990
2003
2003

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 21 publications
(23 reference statements)
8
38
2
Order By: Relevance
“…31P NMR spectroscopy, it is necessary to discuss how our findings relate to those in previous studies. In uterine smooth muscle and brain tissue, phosphoethanolamine was considered to be the major contributor to a large peak in "P NMR spectra (Dawson & Wray, 1985;Tofts & Wray, 1985). Subsequent work confirmed that this peak is due to phosphoethanolamine (Brenton, Garrod, Krywawych, Reynolds, Bachelard, Cox & Morris, 1985;Phoenix & Wray, 1994).…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…31P NMR spectroscopy, it is necessary to discuss how our findings relate to those in previous studies. In uterine smooth muscle and brain tissue, phosphoethanolamine was considered to be the major contributor to a large peak in "P NMR spectra (Dawson & Wray, 1985;Tofts & Wray, 1985). Subsequent work confirmed that this peak is due to phosphoethanolamine (Brenton, Garrod, Krywawych, Reynolds, Bachelard, Cox & Morris, 1985;Phoenix & Wray, 1994).…”
Section: Discussionmentioning
confidence: 64%
“…In a previous study, we showed that the increase in phosphoethanolamine concentration had not occurred 2-4 h postpartum, but by 6 h postpartum it had significantly increased. It was still elevated 12 h postpartum but had fallen 48 h postpartum (Dawson & Wray, 1985;Phoenix & Wray, 1994). The rise in phosphoethanolamine level while the uterus dramatically reduces in size (involution) suggests it may have a role in this process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Peaks were identified on the basis of their resonance positions. Relative metabolite concentrations were obtained from integration of the peaks and corrected for effects of signal saturation using previously obtained factors (Dawson & Wray, 1985). To quantify the metabolite concentrations, a value for ATP under control conditions (1P8 mM) obtained in a previous study (Dawson & Wray, 1985) …”
Section: Animalsmentioning
confidence: 99%